Informed Consent and Autonomy in Doctor-Patient Relationship - Borges, Andréa Moraes (2010)
The informed consent is a process of communication between the doctor and the patient. It is a living process that during the treatment period may be modified under new circumstances that may occur. The doctor must describe to their patients in a simple language that they may understand what their problem is; what treatment is recommend; whether there are any other viable treatment options; the benefits, risks, limitations that might occur with these treatments choices and the consequences of no treatment. After giving the informed consent, the patient agrees to accept the treatment by his/her doctor. Informed consents are acts of autonomous authorizing, so it is important to analyze the concept of autonomy and its relationship to informed consent. Three conditions are necessary by autonomous action: intentionally, understanding and without controlling influences. The actions can be autonomous by degrees, as a function of different satisfaction levels of the conditions about understanding and the lack of controlling influences. Substantial autonomy is a reasonable and achievable goal for decisionmaking and participation in medical interventions.